Experimental Study on the Effect of Addition Micro Additives Zinc Oxide and Graphite Powder at Biodiesel to Decrease the Pressure Drop of Microchannels - Jooned Hendrarsakti; Zido Yuwazama; Putra Andi Kolala; Rico Aditia Prahmana; Alfian Yannu Alfaridzi; Kiki Fadillah Nurul Khotimah; Marianus Beatriks Djala Gili (International Journal of Technology)
Biodiesel is a trend in diesel engines for changing fossil fuels. The diesel engine's important factor is the injector's spray quality. The rise of air-fuel mixing results in a better combustion process. Biodiesel existed as an alternative fuel to change the role of fossil fuels. Palm oil biodiesel is used to experiment with blend B30. The addition of micro additives to biodiesel showed an increase in performance and spray quality. However, the presence of the micro additive may affect the flow characteristics, including pressure drop inside the fuel and injector channel. The current research studied the effect of micro additive materials on biodiesel toward the pressure drop inside the microchannel by replicating the shape and size of the fuel and injector channel. The microchannel is made from a glass tube with an inner diameter of 2.771 mm and 3.614 mm for straight microchannels and a diameter of 2.757 mm, and a 90-degree bend for the bend microchannel. The result showed that adding an additive of graphite powder (GP) and zinc oxide (ZnO) to biodiesel can decrease pressure drop per unit length by up to 59% and 49%, respectively. The data showed a linear relationship between the pressure drop and the Reynolds number. The result affirmed that the friction factor has the same trend as the conventional theory.